2019
DOI: 10.3847/2515-5172/ab4353
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Mass–Radius Relation for Cool Giant Planets

Abstract: Understanding the atmospheres of exoplanets is a milestone to decipher their formation history and potential habitability. High-contrast imaging and spectroscopy of exoplanets is the major pathway towards the goal. Directly imaging of an exoplanet requires high spatial resolution. Interferometry has proven to be an effective way of improving spatial resolution. However, means of combining interferometry, high-contrast imaging, and high-resolution spectroscopy have been rarely explored. To fill in the gap, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…We can do this because the mass-radius relation is nearly flat for the giant planets at the upper edge of the Neptune desert (e.g. Chen & Kipping 2017;Owen & Lai 2018;Thorngren et al 2019). This is because giant planets at the upper edge of the desert are well-approximated by P ∝ ρ 2 polytropes for which the radius does not depend on mass (Stevenson 1982).…”
Section: The Upper Neptune Desert Is Stable Against Mass Lossmentioning
confidence: 99%
“…We can do this because the mass-radius relation is nearly flat for the giant planets at the upper edge of the Neptune desert (e.g. Chen & Kipping 2017;Owen & Lai 2018;Thorngren et al 2019). This is because giant planets at the upper edge of the desert are well-approximated by P ∝ ρ 2 polytropes for which the radius does not depend on mass (Stevenson 1982).…”
Section: The Upper Neptune Desert Is Stable Against Mass Lossmentioning
confidence: 99%
“…Unfortunately, there are no published measurements of the mass of V1298 Tau d. We therefore ran three separate model grids for representative masses of 20 M ⊕ , 50 M ⊕ , and 100 M ⊕ . The latter mass is a rough empirical upper limit from Thorngren et al (2019), who studied an ensemble of older gas giant planets cooler than 1000 K. Planets in their sample with radii comparable to V1298 Tau d have M  100M ⊕ , so we take this as a conservative upper limit on the mass of planet d. On the low-mass end, previous studies of the V1298 system (David et al 2019a(David et al , 2019b have suggested that these planets may have masses closer to those of the sub-Neptune population observed by Kepler (i.e., 1-10 M ⊕ ). This idea is supported by the current ensemble of TTV measurements for this system, which appear to favor M d < 10M ⊕ (Livingston et al 2021, in preparation).…”
Section: Atmospheric Escape Modelingmentioning
confidence: 99%
“…Consequently, strong constraints were derived for short-period gas giants where they had 95% completeness for periods ≤ 3 yrs with a minimum companion mass of ∼ 0.75 M J , which corresponds to a HJ radius of approximately 1.25 R J (Chen & Kipping 2017). Given that the majority of the range is for cool Jupiters, we consider radius as a step function using the Chen & Kipping (2017) for periods < 10 days and Thorngren et al (2019) for periods > 10 days. Within the HJ range, we expect the planets to be inflated thereby increasing the radius.…”
Section: Comparison To Previous Workmentioning
confidence: 99%